2009
DOI: 10.1111/j.1755-3768.2008.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bromfenac ophthalmic solution on ocular inflammation following cataract surgery

Abstract: ABSTRACT.Purpose: This study compared the post-cataract surgery anti-inflammatory effects of topical treatment with 0.1% bromfenac, 0.1% betamethasone or both on postoperative anterior chamber inflammation and corneal swelling. Methods: Seventy-two patients with no eye disease other than cataract were enrolled in a prospective, randomized study to undergo phacoemulsification combined with intraocular lens implantation. After cataract surgery, patients were randomized to treatment with bromfenac, betamethasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 17 publications
5
53
0
1
Order By: Relevance
“…Previous versions of OCT have been found by some to not be as reliable as other methods in determining retinal thickness as it relates to CME [8]. Our findings seem to be consistent with others showing that OCT 3 is highly sensitive in diagnosing subclinical CME [7,[11][12][13]. In this study, CME was defined as foveal and central foveal thickness 2 SD outside the mean.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous versions of OCT have been found by some to not be as reliable as other methods in determining retinal thickness as it relates to CME [8]. Our findings seem to be consistent with others showing that OCT 3 is highly sensitive in diagnosing subclinical CME [7,[11][12][13]. In this study, CME was defined as foveal and central foveal thickness 2 SD outside the mean.…”
Section: Discussionsupporting
confidence: 79%
“…Miyanaga et al [12] reported that bromfenac is effective in minimizing inflammation after cataract surgery. Our study mirrored the findings by Lindstrom [6] and Miyanaga [12]. Our diabetic population was well controlled and the incidence of clinical CME was non-existent and only two were diagnosed subclinically.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Bromfenac ophthalmic solution has received FDA approval based upon the clearance of anterior chamber (AC) inflammation after cataract surgery. 6,7 Recently, Wang et al 29 and Sher et al 30 reported on the role of bromfenac in managing ocular pain and discomfort following refractive surgery. The clinical benefits of bromfenac have been extensively discussed in several comparative studies including the treatment of external or anterior ocular inflammatory diseases, allergic conjunctivitis, as well as postoperative inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Bromfenac, a highly potent inhibitor for both COX-1 and 2 isoforms, belongs to the NSAID class but exhibits unique characteristics 5 that enhances lipophilicity and facilitates its moving across the epithelial layers 5 and prolongs the duration of analgesic and anti-inflammatory effect. 6,7 These superior therapeutic benefits of bromfenac have led to its ophthalmic use especially for the pain and inflammation control after CE. [8][9][10] Oncedaily 11 dosing was previously approved in the USA and Japan and limiting the ocular exposure to bromfenac may result in decreased adverse events (AEs), which is important because, historically, ocular NSAID use has resulted in small numbers of corneal erosions or melts.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier studies which were done, the topical NSAIDs like flurbiprofen ketorolac, bromofenac and diclofenac had been evaluated for their anti-inflammatory actions and the prevention of intraoperative miosis and cystoids macular oedema [15][16][17][18].…”
Section: Group I Flurbiprofenmentioning
confidence: 99%